Analysis of Physicochemical Properties and Volatile Compound of Black Sapote Wine Produced with Saccharomyces cerevisiae Yeast - Hadrian, Edwin; Dewi, Desak Putu Ariska Pradnya; Citragumilang, Adinda Kurnia; Manan, Patricia Agustina; Sandrina, Sandrina (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to develop black sapote wine and alayze its physicochemical properties and volatile compounds. The wine was produced by fermentation using Saccharomyces cerevisiae yeast at different concentrations (0%, 0.5%, and 1%) for seven days. Physicochemical analysis showed pH values of 4.35%, 3.56%, and 3.83%, and titratable acidity values of 0.09%, 0.25%, and 0.2%. Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified several volatile compounds, including alcohols, organic acids, alkanes, and esters. The alcohol group comprised of 20.28%, 61.57% and 34.54%, organic acids 25.5%,14.2%, 20.94%, alkanes 0.69%, 4.44%, 30.61% and esters 2.19%, 12.67%, 6.64% respectively. Fermentation in the production process of black sapote wine has been successful based on its acidity and volatile compound profile.